T-Cell Lymphoma of the Thyroid Gland in Celiac Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
Previous studies have reported the association between celiac disease and T cell lymphoma of the intestine as well as hepatosplenic lymphoma, a specialized peripheral type of T cell lymphoma. In this report, a 66-year-old woman with dermatitis herpetiformis and biopsy-defined celiac disease developed a thyroid mass that proved to be a T cell lymphoma. A T cell lymphoma in the setting of celiac disease appears to be unique. The thyroid gland, due to its shared embryological developmental links with the gastrointestinal tract, is possibly another site of extranodal lymphoma linked to celiac disease.